Development of two forensically important blowfly species (Chrysomya megacephala and Chrysomya rufifacies) (Diptera: Calliphoridae) at four temperatures in India. Issue 4 (25th May 2015) - Bala, Madhu; Singh, Devinder
Abstract The development of the Oriental latrine fly, Chrysomya megacephala (Fabricius), and hairy maggot blowfly, C. rufifacies (Macquart) (Diptera: Calliphoridae), was studied at four different temperatures (22°C, 25°C, 29°C and 31°C) in order to draw correlations between larval age, body length and body dry weight. The mean larval body length increased steadily from a minimum of 1.4 mm for C. megacephala and 1.8 mm for C. rufifacies to a maximum of 17.4 mm for C. megacephala and 15.9 mm for C. rufifacies at different temperatures. Similarly, the mean dry weight increased steadily from a minimum of 0.0007 g for C. megacephala (second instar) and 0.0008 g for C. rufifacies (second instar) to a maximum of 0.0290 g for C. megacephala and 0.0270 g for C. rufifacies at different temperatures. Entomological evidence is often used to estimate the minimum postmortem interval (mPMI) and both of these species are important from a forensic point of view. Graphs of age of larvae vs. body length and age of larvae vs. dry body weight at different temperatures can be used to estimate the larval age of these two species.